Rationalities in Trade Union Practices: A Discourse Analytic Perspective on The Strategies of Three Danish Trade Unions for Professionals - Buch, Anders (Nordic Journal of Working Life Studies, 2015)
The ambition of this paper is to analyze the discursive practices of three Danish trade unions for professional and managerial staff as found in their strategy and position papers. Using discourse analytic methods, the paper analyzes, discusses, and compares the strategy papers of the three unions in order to investigate how they problematize their roles and objectives. This investigation clarifies the discursive premises of the unions and it shows how these premises restrain and afford their agendas. The overall purpose of the paper is to investigate and describe the dominant logics and rationalities that shape the documents and to point to their limits and bounds. Through an archaeological investigation, the paper critically examines the implicit and tacit naturalizations made in the documents and reveals the ideological presuppositions of the discursive practices of the authors. The paper documents how “strategic management” has become an integral part of Danish trade unions practices and the paper sets out to discuss this trend in relation to the general neo-liberal decentering of the “social” and promotion of “community” as the locus of governance. Through examples from the practices of the Danish trade unions for professionals, the paper substantiates how new technologies of governance and the subjectification of union members as “customers” tend to transform the role of the trade unions from the position of “political actors” to “service providers” in the advanced liberal societies.